Inflation in Kazakhstan: an indicator of economic growth or crisis? - Artur Maksimovich Shtro; Amanzhol Dias Azamatylu; Baymetova Zhanar Rakhmatulovna (World Scientific Reports, 2024)
In the light of global economic and political changes related to the Covid-19 pandemic and political conflicts, inflation is one of the discussed economic issues in modern society. The inflation rate is one of the important macroeconomic indicators, which has a negative impact on the activities of all economic entities. Inflation is an integral part of the development of the economies of countries, which appeared at the time of the origin of monetary relations, as it is closely interrelated with concepts such as monetary circulation, financial policy, interest rate, production and consumption. Keeping the inflation rate from rising is one of the main goals of the Central (National) Banks of the world. The article considers the definition of inflation, the causes and consequences of inflation, and presents an analysis of inflation indicators in the economy of Kazakhstan in recent years. The term inflation itself was introduced by the American economist A. Delmar in 1864 and meant a "paper bubble", since at that moment the American monetary circulation was overflowing with banknotes due to the long-lasting civil war in the United States. There is no single definition of the term "inflation” among economists, since inflation is a complex socio-economic phenomenon with a complex of interrelated causes. Analyzing the above, we can conclude that inflation is the process of a general increase in prices for services and goods caused by the prolonged predominance of aggregate demand over aggregate supply, which causes an overflow of the channels of circulation of the money supply in excess of the needs of commodity turnover, as well as a result of a decrease in the purchasing power of the national monetary unit.